The Effectiveness of Sparkol Videoscribe Learning Media in Improving Arabic Vocabulary for Elementary School Students at Islamic Centre Samarinda - Salma Nazhimah; Mustamin, Mustamin; Muhammad Ihsanuddin Masdar (PT. Berkah Smart Academica, 2024)
Sparkol VideoScribe is a cloud-based software that enables teachers to easily create animated videos, providing flexibility in designing learning materials tailored to students' needs. This research aims to examine the effectiveness of Sparkol VideoScribe as a learning media in enhancing Arabic vocabulary for elementary school students at the Islamic Center in Samarinda. The research method employed in this study is a quantitative quasi-experimental design with a Nonequivalent Control Group Design approach. The research sample consisted of 39 students, with 20 students in the experimental group (class 5 ASK) and 19 students in the control group (class 5 AA). Research instruments included tests, observations, and documentation. Data analysis techniques used in this study involved the independent sample t-test and N-Gain test. The results revealed that the post-test scores for the experimental group increased by 27 points from the pre-test score of 55.80 to 82.80. Furthermore, the independent sample t-test resulted in a Sig. 2-tailed value of 0.001 < 0.05, leading to the conclusion that Ha is accepted, and H0 is rejected. The N-Gain value for the experimental group was 0.6145, suggesting that the effectiveness of Sparkol VideoScribe as a learning media in improving Arabic vocabulary for elementary school students at the Islamic Center in Samarinda falls within the category of moderate effectiveness.